Meeting National and Global Health Goals - Utilization of Health Information for Policy Formulation in Iligan City and Oroquieta City - T. Roxas, Alita; D. Jondonero, Man, Clowe; Taculin, Alquine Roy; Q. Lavilles, Rabby (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The study sought to determine the achievements of Iligan City Health District and Oroquieta Interlocal Health Zone (ILHZ) in terms of health related Millenium Development Goals (MDGs) and the National Objectives for Health (NOH) and the functionality of health information as manifested in health resolutions and ordinances; it also sought to assess the data collection, recording, and reporting processes. A triangulation of quantitative and qualitative data, both primary and secondary, was done to meet research objectives. Quantitative data comprised of 2008-2013 data pertaining to health-related MDGs and NOH. Qualitative data on health data capture and reporting, and on the functionality of health information, were obtained through key informant interviews, focus group discussions and assessment of resolutions/ordinances. Findings reveal that the two geographic health areas have met targets for reducing child mortality but are struggling to reduce maternal mortality. Targets on access to safe water by households have similarly been met, but only the Oroquieta ILHZ has met targets for access to basic sanitation. Local decision making with regard to health were generally not in direct response to local health data but as local action to national mandates. Data capture, recording and storage remained largely paper intensive despite the implementation of the web-based Field Health Service Information System (eFHSIS). Recommendations include further training of Barangay Health Workers (BHWs) to enable them to use the eFHSIS, a more active role of the local health boards to influence evidence-based health policies by the LGU, and exploring opportunities in using open data to allow civil society open access to health information thereby enabling greater participation in health affairs.